Bromido(quinolin-8-ol-kappa N-2,O)(quinolin-8-olato-kappa N-2,O)zinc(II) methanol monosolvate - Najafi, E.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, [ZnBr(C9H6NO)(C9H7NO)]center dot CH3OH, has its metal atom N,O-chelated by a neutral and a deprotonated 8-hydroxyquinoline ligand. The hydroxy unit of the neutral ligand is a hydrogen-bond donor to the methanol O atom and the alkoxy O atom of the monoanionic ligand is a hydrogen-bond acceptor to the methanol O atom. In the crystal, adjacent molecules are linked by these two hydrogen bonds, generating a chain running along the a axis.